Pengaruh Literasi Keuangan dan Kemudahan Akses Financial Technology terhadap Kinerja Keuangan UMKM di Medan Tembung - M. A. Jaya Damanik (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the impact of financial literacy and access to financial technology on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Medan Tembung. Using an associative-causal quantitative approach, data was collected from 100 respondents through a structured questionnaire and analyzed using multiple linear regression. The results show that both financial literacy (t = 4.368; p < 0.001) and access to financial technology (t = 3.012; p = 0.003) have a positive and significant impact on the financial performance of MSMEs. This indicates that better knowledge of financial management and easier access to financial technology can improve the financial performance of MSMEs. The research model explains 61.8% (R² = 0.618) of the variation in MSME financial performance, suggesting that both financial literacy and access to financial technology play significant roles in enhancing financial outcomes. This study contributes new insights by integrating individual capacity in financial literacy and access to financial technology as simultaneous factors that strengthen MSMEs, particularly in semi-urban areas. The findings reinforce the financial capability theory, emphasizing the importance of knowledge and access to technology in enhancing individual capabilities and managing finances more effectively. The practical implications of these findings highlight the importance of designing digital-based empowerment programs for MSMEs. These programs should focus on improving financial literacy and facilitating access to financial technology for MSMEs. By implementing this approach, it is expected that MSMEs will be able to manage their finances better, increase operational efficiency, and ensure long-term financial sustainability. The government and related institutions can play a role in providing facilities and training to maximize the benefits of financial technology and improved financial literacy.